2023
DOI: 10.1126/sciadv.ade2232
|View full text |Cite
|
Sign up to set email alerts
|

Abaxial leaf surface-mounted multimodal wearable sensor for continuous plant physiology monitoring

Abstract: Wearable plant sensors hold tremendous potential for smart agriculture. We report a lower leaf surface-attached multimodal wearable sensor for continuous monitoring of plant physiology by tracking both biochemical and biophysical signals of the plant and its microenvironment. Sensors for detecting volatile organic compounds (VOCs), temperature, and humidity are integrated into a single platform. The abaxial leaf attachment position is selected on the basis of the stomata density to improve the sensor signal st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Furthermore, the lightweight sensors did not cause any leaf bending or deformation during the testing period. Notably, previous studies employing similar sensor integration techniques on plant leaves have also reported no noticeable stress on plants or growth inhibition 69 71 .…”
Section: Real-time Plant Measurementsmentioning
confidence: 79%
“…Furthermore, the lightweight sensors did not cause any leaf bending or deformation during the testing period. Notably, previous studies employing similar sensor integration techniques on plant leaves have also reported no noticeable stress on plants or growth inhibition 69 71 .…”
Section: Real-time Plant Measurementsmentioning
confidence: 79%
“…Percolating networks of “rigid” AgNWs and “soft” AuNWs were fabricated as transparent and stretchable strain sensors to solve the inherent trade-offs between sensitivity (GF of 236.6 within 5% strain) and stretchability (over 70%) (Figure e–g) . Hybrid NW systems including AgNW/graphene, AgNW/CNT, AgNW/PEDOT (poly­(3,4-ethylenedioxythiophene)), and AgNW/metal oxide have also been successfully fabricated into metal NW percolation networks for many soft electronics applications. , …”
Section: Low-dimensional Nanomaterialsmentioning
confidence: 99%
“…[ 16,17 ] For instance, an electronic wearable sensor has been mounted on the leaves of plants to detect viral and fungal infections or stresses such as salinity or drought. [ 18 ] This sensor chip was tested with tomato plants infected with three different pathogens, tomato spotted wilt virus, early blight, and late blight, by exposing them to a variety of abiotic stresses. [ 18 ] Moreover, it is worth noting that wearable electronics equipped with 3D nanoprinting technology [ 19 ] for plant health monitoring are currently emerging in the field.…”
Section: Introductionmentioning
confidence: 99%
“…[ 18 ] This sensor chip was tested with tomato plants infected with three different pathogens, tomato spotted wilt virus, early blight, and late blight, by exposing them to a variety of abiotic stresses. [ 18 ] Moreover, it is worth noting that wearable electronics equipped with 3D nanoprinting technology [ 19 ] for plant health monitoring are currently emerging in the field. This is mainly because of two inherent features: customizability and miniaturization.…”
Section: Introductionmentioning
confidence: 99%